2003
DOI: 10.2466/pms.2003.96.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup Analysis of Sex Difference on the Vandenberg-Kuse Mental Rotation Test

Abstract: A large sex difference has been elicited on the Vandenberg-Kuse mental rotation test. Prior research emphasizes the biological root of this sex difference. In recent experiments we confirmed this viewpoint. A large sample was administered the test, and the distributions of scores for men and women (N = 138; 68 men and 70 women: ages 19 to 23 years). The mean scores were used as cut-off points to group the men and the women in different subgroups (Low/Women, High/Women, Low/Men, High/Men). There were large diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Among the explored cognitive domains, the visuospatial abilities hold a prominent position. In particular, several studies have shown sex-based differences in the visuospatial domain with men performing better than women (Vandenberg & Kuse, 1978 ; Linn & Peterson, 1985 ; Johnson & Meade, 1987 ; Goldstein et al, 1990 ; Voyer et al, 1995 ; Karádi et al, 2003 ; Peters, 2005 ). Neuroimaging investigations revealed that during a Mental Rotation Test (MRT), men activate parietal cortex more than women who, in their turn, exhibit a more marked activation in the inferior frontal cortex (Hugdahl et al, 2006 ).…”
mentioning
confidence: 99%
“…Among the explored cognitive domains, the visuospatial abilities hold a prominent position. In particular, several studies have shown sex-based differences in the visuospatial domain with men performing better than women (Vandenberg & Kuse, 1978 ; Linn & Peterson, 1985 ; Johnson & Meade, 1987 ; Goldstein et al, 1990 ; Voyer et al, 1995 ; Karádi et al, 2003 ; Peters, 2005 ). Neuroimaging investigations revealed that during a Mental Rotation Test (MRT), men activate parietal cortex more than women who, in their turn, exhibit a more marked activation in the inferior frontal cortex (Hugdahl et al, 2006 ).…”
mentioning
confidence: 99%